Hubungan Pola Asuh Demokratis Orang Tua terhadap Perkembangan Sosial Emosional Anak Usia 4-5 Tahun - Dwi Amanda, Dea; Syafitri, Yuni; Wahyuni, Desvi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The aim of this research is whether there is a relationship between democratic parenting styles and the social emotions of early childhood. Parenting patterns in the family have an important role in a child’s growth. So the parenting pattern usually applied by parents is democratic parenting. This research uses quantitative research methods with descriptive data analysis techniques. One parenting style that has proven to be very beneficial in this regard is democratic parenting. This approach emphasizes open communication, mutual respect, and active involvement in the decision-making process. By adopting a democratic parenting style, parents create an environment that fosters their children’s social and emotional growth in several significant ways. It can be concluded that choosing an appropriate and good parenting pattern is one of the determining factors in helping the social-emotional development of early childhood, namely democratic parenting.